2016
DOI: 10.1080/14653125.2016.1229846
|View full text |Cite
|
Sign up to set email alerts
|

A qualitative study of work-life balance amongst specialist orthodontists in the United Kingdom

Abstract: Objective: To identify factors affecting work-life balance amongst male and female orthodontists in the United Kingdom. Design: A qualitative interview-based study with a cross-sectional design.Subjects: Specialist orthodontists working in specialist practice and the hospital service in the United Kingdom were selected by purposive sampling. Methods: In-depth semi-structured interviews were conducted with eighteen orthodontic specialists. Interview transcripts were analysed using Framework Analysis. Results: F… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
19
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 14 publications
(23 citation statements)
references
References 18 publications
(19 reference statements)
4
19
0
Order By: Relevance
“…The equitable distribution of work and rest times accounts for the equilibrium between personal and work life mandatory for a good QOL, despite the multiple factors that may affect this balance. 26 Dentistry and its specialties are autonomous professions hence the decision to distribute time will depend on the free choosing of the professional, conditioned by their needs and the environment. 26 Also work dissatisfaction of orthodontists has been reported on aspects related with management of the practice and the amount of personal time, reinforcing the influence of work conditions on work satisfaction and consequently QOL.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The equitable distribution of work and rest times accounts for the equilibrium between personal and work life mandatory for a good QOL, despite the multiple factors that may affect this balance. 26 Dentistry and its specialties are autonomous professions hence the decision to distribute time will depend on the free choosing of the professional, conditioned by their needs and the environment. 26 Also work dissatisfaction of orthodontists has been reported on aspects related with management of the practice and the amount of personal time, reinforcing the influence of work conditions on work satisfaction and consequently QOL.…”
Section: Discussionmentioning
confidence: 99%
“…26 Dentistry and its specialties are autonomous professions hence the decision to distribute time will depend on the free choosing of the professional, conditioned by their needs and the environment. 26 Also work dissatisfaction of orthodontists has been reported on aspects related with management of the practice and the amount of personal time, reinforcing the influence of work conditions on work satisfaction and consequently QOL. [27][28][29][30] In this study, activities of teaching/researching positively influenced QOL in the physical and psychological dimensions.…”
Section: Discussionmentioning
confidence: 99%
“…These theories explain the relationship between work and family and other variables (Ransome, 2007; Beigi et al , 2018) and reinforce the work–family conceptual positioning of this study. For instance, work–family conflicts focus on problems created because of pressures from work and family that are incompatible (Netemeyer et al , 1996; Adame et al , 2015; Bateman et al , 2016; Pradhan, 2016). This would also include other variables faced by members of non-family households.…”
Section: Literature Reviewmentioning
confidence: 99%
“…One of the ongoing discussions that reveal this is work–family balance, which is integrated as part of the work–life balance phenomenon. In response to concerns about work–life balance, job satisfaction and career advancement of women, studies (Frone et al , 1992; Goff et al , 1990; Netemeyer et al , 1996; Adame et al , 2015; Bateman et al , 2016) have established the conflict between family duties and career demands. This conflict arises because some aspects of work and family roles are incompatible (Adame et al , 2015), and depend on the career or family stage of women (Beigi et al , 2018).…”
Section: Introductionmentioning
confidence: 99%
“…Although several studies have reported high job satisfaction among orthodontists, [1][2][3] career satisfaction, and balance of work and other facets of life may be negatively impacted by various constraining influences.…”
Section: Introductionmentioning
confidence: 99%